Annotated check-list, generic key and new species of Old World Deltocephalini leafhoppers with nomenclatorial changes in the Deltocephalus group and other Deltocephalinae (Hemiptera, Auchenorrhyncha, Cicadellidae) - Webb, Michael D.; Viraktamath, Chandra A. (Zootaxa, 2009)
An annotated check-list and generic key to Old World members of the grassland leafhopper tribe Deltocephalini are provided. The Deltocephalus group of genera are discussed and one of the included genera, Recilia Edwards, is revised to include only two species, coronifer (Marshall) (= coroniceps Kirschbaum) and raoi (Dash & Viraktamath), comb. nov. (from Deltocephalus (Recilia)). All other species of Recilia are placed in Maiestas Distant, 1917, resulting in several new combinations (see species lists under Maiestas) and the following new junior synonyms of Maiestas: Togacephalus Matsumura 1940 syn. nov., Inazuma Ishihara, 1953, syn. nov., Inemadara Ishihara, 1953, syn. nov., and Insulanus Linnavuori, 1960a, syn. nov. The following additional new nomenclatorial changes are proposed (all new combinations from Deltocephalus): Athysanini: Allophleps eques (Jacobi), comb. nov., Bampurius melichari (Distant), comb. nov., Monobazus fuscovarius (Distant), comb. nov., Okaundua ornatula (Melichar) comb. nov.; Paralimnini: Wakaya angustus (Melichar), comb. nov., Wakaya severa (Melichar), comb. nov., Vilargus campanus (Naudé), comb. nov., Platentomus aristida (Cogan), comb. nov.; Stenometopiini: Stirellus coloratus (Distant), comb. nov., Stirellus laetus (Melichar), comb. nov., Stirellus rufolineatus (Melichar), comb. nov. , Deltocephalus alacer Stål, 1859, junior synonym of Hecalus porrectus (Walker, 1858), syn. nov., Thamnotettix prabha Pruthi, 1930: 62, junior synonym of Maiestas maculata (Pruthi, 1930: 58-59), syn. nov. Polyamia drepananiforma Zhang & Duan, 2004, junior synonym of Matsumuratettix hiroglyphicus Matsumura, 1914, syn. nov., Scaphoideus seychellensis Distant, 1917, junior synonym of Maiestas vagans (Distant, 1917), syn. nov., Recilia dolabra Kramer, August 1962 and R. jordanica Dlabola, 1965, junior synonyms of Maiestas angustisecta (Linnavuori, 20th August 1962), syn. nov., Deltocephalus immaculatus Melichar, 1914, status revised from Deltocephalus porticus immaculatus Melichar. In addition, Pingellus Evans (1966) and Occiplanocephalus Evans (1942) are transferred from Deltocephalini to Athysanini (new placements) and three new species (Maiestas dashi sp. nov., M. knighti sp. nov. and Paramesodes iraniensis sp. nov.) are described with figures provided for these and other species.